Injection-site lesion prevalence and potential risk factors in UK beef cattle - Cresswell, E.; Remnant, J.G.; Butterworth, A.; Wapenaar, Wendela (BMJ Publishing Group, 2016)
Injectable veterinary medicinal products (VMPs) are widely used in cattle in the UK, and in particular vaccines are often used on large numbers of animals in the herd. The formation of injection-site lesions (ISLs) is a risk when using injectable products and has potential consequences for meat quality, animal welfare and beef industry income. This study used carcase observation in four abattoirs in England to determine ISL prevalence in beef cattle. Additionally, a questionnaire survey was used to investigate vaccination technique among UK beef farmers. The ISL prevalence was 4.1 per cent (95 per cent CI 3.4 per cent to 4.9 per cent). A potential difference between sites being used for vaccination and the distribution of ISLs on carcases suggested that factors other than vaccination were contributing to ISL incidence. Questionnaire responses highlighted deficits in good vaccination practices such as using the recommended site of injection and needle hygiene. The role of the veterinarian in knowledge transfer is crucial in providing practical injection advice when prescribing vaccines and other VMPs. This study identified factors to address when aiming to reduce ISL formation in UK beef animals.